RESEARCH MODELS OF GREEN TOURISM DEVELOPMENT - N. Yu. Rasulova (Journals Park Publishing, 2024)
The article examines the problems of the effective use of research models of green tourism development. In particular, issues of the importance of green tourism in the protection of the environment and the rational use of Natural Resources, the effective use of the green touristic capabilities of the regions in forming a “green” economy have been scientifically analyzed. Scientific proposals and conclusions on the development of the field are also presented.
Keywords: green tourism, CO2, green economy, Environmental Kuznets Curve analysis, green tourism opportunities.